2011
DOI: 10.1007/s10549-011-1782-x
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy inhibits development and progression of mammary tumours in immunocompetent mice

Abstract: We have determined the effect of combining the chemotherapy agent doxorubicin and the anti-resorptive drug zoledronic acid on the early stages of spontaneous mammary tumour development using the immunocompetent PyMT mouse model that closely mimics human breast cancer development. 6-week-old PyMT mice were treated weekly for 6 weeks with PBS, 2 mg/kg doxorubicin, 100 μg/kg zoledronic acid or doxorubicin followed 24 h later by zoledronic acid (n = 15/group). Untreated, 6-week-old animals were used for comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…ZOL is shown to inhibit migration and invasion of ER-ve breast cancer cells but has comparatively modest inhibitory effects on ER?ve cells in vitro [36][37][38]. In agreement with this, we found no effects of ZOL on migration or invasion of MCF7 or T47D cells in vitro (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…ZOL is shown to inhibit migration and invasion of ER-ve breast cancer cells but has comparatively modest inhibitory effects on ER?ve cells in vitro [36][37][38]. In agreement with this, we found no effects of ZOL on migration or invasion of MCF7 or T47D cells in vitro (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…Ottewell et al reported that the inhibition of tumor growth was observed by sequential injection with DXR and ZOL in a mouse model of breast and mammary tumor (31,32). They concluded that sequential treatment with DXR followed by ZOL elicited substantial antitumor effects in vivo, but ZOL followed by DXR did not (31).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that day 5 is too late, and any early antitumor effects of ZOL may have been missed and, in addition, the time of peak increase in apoptosis may be variable between patients. In the preclinical studies reporting increased levels of tumor cell apoptosis following the addition of ZOL to chemotherapy, tumors were always collected 24 hours after the last of 6 weekly injections of ZOL (4,6,7). Following a 4 mg intravenous dose of ZOL administered over 15 minutes, there is a sharp increase in concentration with a peak plasma concentration after the end of infusion of approximately 1 mmol/L (23) followed by a rapid decline in plasma concentration with prolonged (terminal elimination half-life approximately 7 days) but very low-drug plasma concentrations thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor effects included increased tumor cell apoptosis, reduced tumor proliferation, and inhibition of tumor vascularization (4). The same treatment schedule has also been shown to prevent the development and progression of spontaneous mammary tumors in the immunocompetent PyMT mouse model, again in the absence of bone disease (7).…”
Section: Introductionmentioning
confidence: 99%